Quantification of a mechatronic pneumatic gripping system for a multi-link robot manipulator - Yemelianov, Dmytro; Shevchenko, Serhii; Kryvoplias-Volodina, Liudmyla (My University, 2023)
The basis of the work is the tasks related to the synthesis of working bodies for moving artificial food, and the development of a control program for them based on PLC - namely, pneumatic grippers. An urgent task was also to ensure the movement of products processed by a robot manipulator according to the given law of movement. Based on the study of the dynamic characteristics of the drive and the control system of the power part of the position electro-pneumatic drive. Mathematical and computer modeling methods, methods of solving ordinary differential equations and partial differential equations, correlation analysis method are used. Analytical dependencies were obtained for controlling the drive of a robot-manipulator with a pneumatically controlled gripper to determine the kinematic parameters of the product movement during processing. The dynamic model of the pneumatic gripper and its drive was mathematically tested. The law of motion of the final link of the manipulator, close to the optimal speed, was obtained. On the basis of the research calculations and the analysis of the functional mechatronic modules, the energy efficiency of the proposed control scheme of the power part of the positional pneumatic drive was confirmed. The result of the study of the electropneumatic positional drive is presented in the form of an algorithm and a special program for calculating and comparing the kinematic and dynamic parameters of the drive.The technological time of the operation is adjustable and when using the exhaust cross-section of the working chambers of the pneumatic cylinder - 4 mm, the value of the working pressure up to 7 bar, the movement of the rod - up to 200 mm, it has optimal kinematic characteristics of work for a pneumatic gripper. The discrepancy between the value of the time of the working stroke of the output link of the functional mechatronic module calculated during the mathematical modeling after working out the kinematic cycle of the gripper was up to 3% for various input parameters.

В основу роботи покладено задачі, пов'язані з синтезом робочих органів для переміщення штучних харчових продуктів, та розробкою програми керування ними на базі ПЛК - а саме, пневматичних захватів. Актуальним завданням було також забезпечення переміщення продуктів, що обробляються роботом-маніпулятором, за заданим законом руху. В основу роботи покладено дослідження динамічних характеристик приводу та системи керування силовою частиною позиційного електропневматичного приводу. Використано методи математичного та комп'ютерного моделювання, методи розв'язання звичайних диференціальних рівнянь та рівнянь в частинних похідних, метод кореляційного аналізу. Отримано аналітичні залежності для керування приводом робота-маніпулятора з пневмокерованим захватом для визначення кінематичних параметрів руху виробу в процесі обробки. Проведено математичну апробацію динамічної моделі пневматичного захвату та його приводу. Отримано закон руху кінцевої ланки маніпулятора, близький до оптимальної швидкості. На основі проведених дослідницьких розрахунків та аналізу функціональних мехатронних модулів підтверджено енергоефективність запропонованої схеми керування силовою частиною позиційного пневмоприводу. Результат дослідження електропневматичного позиційного приводу представлено у вигляді алгоритму та спеціальної програми для розрахунку та порівняння кінематичних і динамічних параметрів приводу. Технологічний час виконання операції регулюється і при використанні вихідного перерізу робочих камер пневмоциліндра - 4 мм, величини робочого тиску до 7 бар, переміщення штока - до 200 мм має оптимальні кінематичні характеристики роботи для пневматичного захоплювача. Розбіжність між значенням часу робочого ходу вихідної ланки функціонального мехатронного модуля, розрахованим під час математичного моделювання, після відпрацювання кінематичного циклу роботи захвату склала до 3% для різних вхідних параметрів.
Keywords: кафедра мехатроніки та пакувальної техніки; functional; module; pneumatic gripper; electro-pneumatic drive; precision; variable gripper soft pads; функціональний; модуль; пневматичний захват; електропневматичний привод; точність; м'які накладки зі змінним захопленням